TaqI polymorphism of the VDR gene: aspects related to the clinical behavior of COVID-19 in Cuban patients - Estela Morales Peralta (SpringerOpen, 2021)
Abstract Purpose To determine the relationship between the genotypes of the TaqI polymorphism of VDR gene and the clinical forms of COVID-19 in Cuban patients. Methods TaqI polymorphism was determined by the PCR in 104 Cuban patients, who suffered different clinical forms of COVID-19. Results There was a greater possibility of presenting symptomatic forms [OR = 2.081, 95% CI: 0.243–17.842], even severe [OR = 1.200, 95% CI: 0.217–6.638], related to the tt genotype. Conclusion There are signs of association between the risk of developing COVID-19 and the genotypes of the TaqI polymorphism of the VDR gene in the studied Cuban patients.